Effect of angiotensin-converting enzyme inhibition on endothelial function and insulin sensitivity in hypertensive patients - YAVUZ, DİLEK; KOÇ, MEHMET (J R A A S LTD, 2003)
Introduction Evidence suggests an association between insulin resistance, hypertension and impaired endothelial function. Studies have shown that insulin resistance precedes the development of hypertension. By improving insulin sensitivity, it may be possible to improve hypertension and the subsequent damage to vessel walls. Some data indicates beneficial effects of angiotensin-converting enzyme (ACE) inhibitors on insulin sensitivity and endothelial function. We aimed to investigate these effects of ACE inhibition in the same group of patients with essential hypertension. Materials and methods Nine non-smoking, untreated hypertensive patients (38.3+/-9 years, 4/5 male/female) and 12 age-matched healthy subjects (35.2+/-6.7 years, 5/7 male/female) were included in the study. Hypertensive patients were given enalapril maleate (5-40 mg/day) for six months. The following parameters were studied at baseline and at the end of treatment period. Whole body insulin sensitivity was measured by a formula derived from an oral glucose tolerance test and named as the insulin sensitivity index (ISI). Insulin was measured by chemiluminescence and glucose by a glucose oxidase method. Endothelial function was evaluated as flow-mediated dilatation (FMD) of the brachial artery by ultrasonography and expressed as a percentage change relative to baseline diameter. Endothelial-independent vasodilatation was measured after sublingual nitroglycerine. Results FMD was impaired in the hypertensive group compared with healthy subjects (7.3+/-3.1% vs. 15.3+/-4.8%, p<0.0005), and ISI values were 1.18+/-0.6 vs. 4.4+/-0.9 (p<0.0001) respectively. Both insulin sensitivity and FMD improved after the treatment period compared with baseline values, FMD increased from 7.3+/-3.1% to 16.0+/-2.9% (p<0.0005) and ISI from 1.18+/-0.6 to 4.2+/-1.0 (p<0.0001). FMD and ISI showed a significant positive correlation (r=0.67, p<0.001) in the hypertensive group. Conclusions Patients with essential hypertension have impaired endothelial function and decreased whole body insulin sensitivity compared with healthy subjects. Treatment for six months with enalapril maleate seems to improve both FMD and ISI. This Study confirms the beneficial effects of ACE inhibition on both endothelial function and insulin sensitivity tested in the same group of essential hypertensive patients. The mechanism of these favourable effects of ACE inhibition needs to be clarified.
Keywords: ACE inhibition; endothelial dysfunction; insulin sensitivity; DEPENDENT DIABETES-MELLITUS; ACE-INHIBITION; II ANTAGONISM; DYSFUNCTION; RESISTANCE; DISEASE; MECHANISMS; SYSTEM; VASODILATION; IMPROVEMENT